A Clinical Update of the Hb Siirt [β27(B9)Ala→Gly; HBB: c.83C>G] Hemoglobin Variant. (2nd January 2017) - Cappabianca, Maria Pia; Colosimo, Alessia; Sabatucci, Annalaura; Dainese, Enrico; Di Biagio, Paola; Piscitelli, Roberta; Sarra, Ofelia; Zei, Daniela; Amato, Antonio
Abstract: We report a clinical update of the hemoglobin (Hb) variant [β27(B9)Ala→Gly; HBB : c.83C>G], named Hb Siirt, that was previously described as a silent variant in a 23-year-old Kurdish female. The patient was also a carrier of the codon 5 (–CT) ( HBB : c.17_18delCT) frameshift mutation and of the ααα anti 3.7 triplication. Her initial moderate β-thalassemia intermedia (β-TI) phenotype worsened with time, causing the patient to become a transfusion-dependent subject at the age of ∼40 years. Subsequent molecular characterization of both parents revealed that the Hb Siirt variant was inherited by the mother, while the other two globin alterations ( HBB : c.17_18delCT and ααα anti 3.7 triplication) were genetically transmitted by the father. The latter remained a carrier of a mild β-TI phenotype throughout his life, at least until the age of 65 years. We hypothesize that the worsened clinical conditions in the daughter were due to the additional, maternally inherited Hb Siirt variant. However, protein 3D conformational analysis did not seem to reveal substantial overall structural changes. Among the other three described variants [Hb Volga ( HBB : c.83C>A), Hb Knossos ( HBB : c.82 G>T), Hb Grange-Blanche ( HBB : c.83C>T] that are due to nucleotide substitutions at codon 27 of the β-globin gene; only Hb Knossos causes a β + -thalassemia (β + -thal) phenotype.